Speaking across the curriculum : practical ideas for incorporating listening and speaking into the classroom. (International Debate Education Association, 2004)
Speaking Across the Curriculum gives teachers ready-made speaking and listening activities that can be infused into any curriculum. Over 50 activities help teachers encourage debate and discussion and teach students speaking and listening skills.